Twitter Please Do Your Magic: The Vulnerability of Fraud Victims On the Social Media - Yahya, Azzahra; Zaky, Muhammad (Deviance Jurnal Kriminologi, 2023)
For Twitter users, the term “Twitter Please Do Your Magic” is familiar. This means that with good delivery and communication, even Twitter accounts have the same potentials in solving problems raised. In reality, crime always finds its own loophole. The existence of this trend is used by irresponsible parties as part of the fraud mode by forming a narrative that is able to bring disadvantages to humanity. Therefore, as an effort to understand this, an assessment of the characteristics of the victims was carried out using the perspective of lifestyle-exposure criminology theory. Using a qualitative research method by taking a fraud case study on twitter accounts, the researchers utilized data from interviews with four victims, a witness resource person and an expert. The result was that the victims of the case study have some characteristics in common related to each other, which has the potential to endanger their lives in explaining the cause of the victim's position. Among them, first, making twitter their favorite social media among all other social media they have. Second, the victims like content topics related to social issues supported by their involvement in previous donation activities. Third, the victims have the right and access to their own finances. Fourth, the victims have a "common thread" with perpetrators such as a sense of closeness and similarity. Finally, the fifth, the victims tend to trust their online friends on twitter. Although these results cannot be generalized to all cases of "Twitter Please Do Your Magic" fraud that have occurred, at least this research is expected help understand problems surrounding the issue, especially from the perspective of the victims.